1993
DOI: 10.1079/bjn19930124
|View full text |Cite
|
Sign up to set email alerts
|

Antinutritive effects of wheat-germ agglutinin and other N-acetylglucosamine-specific lectins

Abstract: Incorporation of N-acetylglucosamine-specific agglutinins from wheat germ (Triticum aestivurn ; WGA), thorn apple (Datuva stvarnoniurn) or nettle (Uvtica dioica) rhizomes in the diet at the level of 7 g/kg reduced the apparent digestibility and utilization of dietary proteins and the growth of rats, with WGA being the most damaging. As a result of their binding and endocytosis by the epithelial cells of the small intestine, all three lectins were growth factors for the gut and interfered with its metabolism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 18 publications
1
79
0
2
Order By: Relevance
“…In other animals, soybean or other plant lectins have also been reported to cause hyperplastic growth of intes ajiri et Pusztai et al, 1990;Bardocz et al, 1992 andBanwell et a 1993); decreased cell turnover time (Pusztai et al, 1990); uptake of lectin via endocytosis intestinal epithelial cells (Pusztai et al, 1981;Banwell et al, 1984;King et al, 1986;Bardoc et al, 1995); changes in pancreatic weight and enzyme secretion (Greer and Pusztai, 1985;Huisman et al, 1990;Banwell et al, 1993;Pusztai et al, 1993a;Grant et al, 1997); changes in liver weight (Oliveira et al, 1988;Aletor, 1989); reduced plasma insulin levels (Knott et al, 1992;Bardocz et al, 1996;Pusztai et al, 1998); increased cholecystokinin (CCK) release (Jordinson et al, 1996 and; and reduced skeletal muscle mass (Oliveira et al, 1988;Bardocz et al, 1992).…”
Section: Biological Effects In Fish General Considerationsmentioning
confidence: 99%
“…In other animals, soybean or other plant lectins have also been reported to cause hyperplastic growth of intes ajiri et Pusztai et al, 1990;Bardocz et al, 1992 andBanwell et a 1993); decreased cell turnover time (Pusztai et al, 1990); uptake of lectin via endocytosis intestinal epithelial cells (Pusztai et al, 1981;Banwell et al, 1984;King et al, 1986;Bardoc et al, 1995); changes in pancreatic weight and enzyme secretion (Greer and Pusztai, 1985;Huisman et al, 1990;Banwell et al, 1993;Pusztai et al, 1993a;Grant et al, 1997); changes in liver weight (Oliveira et al, 1988;Aletor, 1989); reduced plasma insulin levels (Knott et al, 1992;Bardocz et al, 1996;Pusztai et al, 1998); increased cholecystokinin (CCK) release (Jordinson et al, 1996 and; and reduced skeletal muscle mass (Oliveira et al, 1988;Bardocz et al, 1992).…”
Section: Biological Effects In Fish General Considerationsmentioning
confidence: 99%
“…11 At very high concentrations, several of these lectins have antinutritive effects, with altered gastrointestinal morphology and malabsorption. 11,23 The precise dose of WGA delivered in the current study was unknown but may have been as high as ϳ 60 mg per day. Although Lorernzsonn and Olsen 24 have reported that even larger doses of purified WGA (200 mg per day) can be ingested for short periods of time without ill effect, a detailed evaluation of possible malabsorption was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…109, 1995 turb the normal function of the intestine. In addition, some cause systemic effects such as an enlargement of the pancreas (Pusztai et al, 1993). These lectins may also play a role in the defense against predators.…”
Section: The Toxlclty Of Plant Lectins For Hicher Animalsmentioning
confidence: 99%